(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Sensorineural hearing loss (SNHL) is hearing loss caused by damage to the cochlea or retrochoclea. This hearing loss can affect any age with a variety of different etiologies. Common causes of SNHL include exposure to loud noises, genetic factors, or the natural aging process. WHO has launched the Sound Hearing 2030-Better Hearing for All program which is an initiative program in efforts to prevent and reduce hearing loss. This program aims to reduce hearing problems by 90% by 2030. The aim of this study was to analyze the characteristics of people with Sensorineural Deafness at the ORL-HNSClinic of Roemani Hospital. This study used a descriptive retrospective research method using secondary data from the patient’s medical records. This study used a cross sectional approach research design with the sampling technique using purposive sampling technique. The most distribution of Sensorineural Deafness at Roemani Hospital is in the age group> 50 years 81.8%, men suffer more sensorineural deafness 57.6%, the group of people who do not work 84.8%, bilateral 76.8% than unilateral 23.2%, degree of severe hearing loss 65.7%, no history of comorbid disease 72.7%, no history of taking ototoxic drugs 100%, no history of trauma 100%. The most distribution of Sensorineural Deafness at Roemani Hospital is in the age group> 50 years, men, who do not work, in both ears or bilateral, severe degree, do not have a history of comorbid diseases, do not have a history of taking ototoxic drugs, do not have history of trauma.